2006
DOI: 10.1161/01.atv.0000245808.12493.40
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Postprandial Hypertriglyceridemic Rabbit Exhibits Insulin Resistance and Central Obesity

Abstract: Objective-We have established a hereditary postprandial hypertriglyceridemic (PHT) rabbit. The present study was designed to define whether this rabbit model represents both insulin resistance and central obesity. Methods and Results-Body weight, abdominal circumference, visceral fat weight, and glucose tolerance were compared between PHT and Japanese white (JW) rabbit. Plasma levels of triglycerides (TG), total cholesterol (TC), glucose, and insulin were measured before and after feeding. Abdominal circumfere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 31 publications
2
41
0
Order By: Relevance
“…Our results indicated a marked hyperinsulinaemia at baseline in castrated-obese rabbits which is consistent with other data in obese rabbits (Kawai et al, 2006;Zheng et al, 2009). Obesity-induced fasting hyperinsulinaemia has been also described in cats (Thiess et al, 2004;Appleton et al, 2005), dogs (Verkest et al, 2005;Verkest et al, 2011) and humans (Festa et al, 2008;DeFronzo & Tripathy, 2009;Gil-Campos et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results indicated a marked hyperinsulinaemia at baseline in castrated-obese rabbits which is consistent with other data in obese rabbits (Kawai et al, 2006;Zheng et al, 2009). Obesity-induced fasting hyperinsulinaemia has been also described in cats (Thiess et al, 2004;Appleton et al, 2005), dogs (Verkest et al, 2005;Verkest et al, 2011) and humans (Festa et al, 2008;DeFronzo & Tripathy, 2009;Gil-Campos et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…At the same time, many features of lipoprotein metabolism in rabbits are similar to those in humans (so-called LDL mammals) but differ from the most widely used experimental animals -rats and mice, which are predominantly HDL animals (Kitajima et al, 2004;Zheng et al, 2009;Waqar et al, 2010). That is why rabbits are increasingly used as appropriate animal models to study pathogenic mechanisms of obesityassociated abnormalities in lipid and glucose metabolism such as insulin resistance, dyslipidaemia, atherosclerosis, metabolic syndrome and type 2 diabetes (Kainuma et al, 2006;Kawai et al, 2006;Zhao et al, 2007;Waqar et al, 2010). Therefore, there is an increasing need to apply simple and reliable markers for evaluation of insulin sensitivity and β-cell function in rabbits.…”
Section: Introductionmentioning
confidence: 99%
“…Blood samples were collected through ear veins 0, 5, 10, 20, 30, 60 and 120 min after the glucose was administered. The oral glucose tolerance test (OGTT) was performed as described previously [13]. After 16 hours’ fasting, rabbits were administered a glucose solution (1.5 g/kg body weight) orally.…”
Section: Methodsmentioning
confidence: 99%
“…However, in rabbits, lipoprotein metabolism resembles that in humans [11,12]. The postprandial hyperlipidemic rabbit shows intraperitoneal fat accumulation, insulin resistance and postprandial hypertriglyceridemia [13], mimicking human metabolic syndrome, although no atherosclerotic lesions develop. Recently, Waqar et al [14] reported that a high-fat diet induced metabolic syndrome and atherosclerosis in rabbits.…”
Section: Introductionmentioning
confidence: 99%
“…Blood samples were centrifuged at 2,000 rpm for 10 min, at 4 ° C. The plasma TG and total cholesterol (TC) levels were measured by Abbott Vision kits (Dinabot, Ltd., Tokyo, Japan) [12] .…”
Section: Analysis Of Plasma Lipids and Enzyme Activitymentioning
confidence: 99%